Rethinking the words hotspot reservoir and pristine in the environmental dimensions of antimicrobial resistance - Richard Helliwell; Isabel Ewin; Alexander D. Williams; Diane T. Levine; Andrew C. Singer; Sujatha Raman; Carol Morris; Dov J. Stekel (npj Antimicrobials and Resistance)
Abstract We assess three words commonly used to represent the environmental dimensions of antimicrobial resistance (AMR) – ‘hotspot’, ‘reservoir’ and ‘pristine’ – through two questions: how are these terms used in published research; and how do these terms shape research being conducted? We advocate for the community to reflect on and improve its use of language, and suggest four potentially more productive and precise terms for AMR hazard: prevalence; transmission; evolution and connectivity.